IMPLEMENTASI WAKAF PRODUKTIF DI PESANTREN PEMBERDAYAAN AL MUHTADIIN DALAM MENINGKATKAN PEREKONOMIAN MASYARAKAT DESA CIKANGKUNG, CIRACAP,SUKABUMI - Fadlatul Wasilah; Norma Rosyidah (ICO EDUSHA, 2022)
Waqf is one of the instruments that exist in Islamic teachings and has been proven to be able to overcome problems and improve people's welfare. The majority of Muslim communities in Indonesia still understand that waqf is only limited to 3M, namely mosques, schools, and cemeteries. Whereas the use of waqf assets needs to be optimized so that it can be productive to improve people's welfare. The purpose of this study was to determine the implementation of productive waqf in the Al Muhtadiin Empowerment Islamic Boarding School and its impact on the economic conditions of the surrounding community. The research method used is descriptive qualitative. The results of the study: (a). In general, the management of productive waqf management has been carried out properly and professionally by the administrators of the Al-Muhtadiin Empowerment Islamic Boarding School (b). The results of productive waqf management by the Al-Muhtadiin empowering Islamic boarding school have proven to be able to improve the community's economy, especially the Cikangkung Village area, Ciracap District, Sukabumi Regency, West Java. Keywords: Productive Waqf, Management, Economy References Aisyah, Lisda, Agus Alimuddin, dan Bambang Suhada. “Implementasi Wakaf Produktif untuk Meningkatkan Kesejahteraan Masyarakat” 3 (Oktober 2020). Ali, Muhammad Daud. Sistem Ekonomi Islam. Jakarta: Universitas Indonesia, 1988. Bapak Anggriansyah Munggaran. Zoom Online, 12 Oktober 2022. “Data Tanah Wakaf Bersertifikat di Indonesia.” Badan Wakaf Indonesia, 2019. Miles, Matthew B, dan A. Michael Huberman. Qualitative Data. London: SAGE Publications, 1994. “Persentase Penduduk Miskin Maret 2022 turun menjadi 9,54 persen.” Badan Pusat Statistik, 2022. Pesantren Pemberdayaan Al Muhtadiin. “Pesantren Pemberdayaan Al-Muhtadiin,” t.t. Diakses 14 November 2022. Purnomo, Agus, dan Luthfi Khakim. “Implementasi Wakaf Produktif dalam Perspektif Ekonomi Syariah.” Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam 16 (2019). Purwaningsih, Septi, dan Dewi Susilowati. “Peran Wakaf dalam Meningkatkan Pemberdayaan Ekonomi Umat.” Jurnal Ekonomi Bisnis dan Akuntansi 22 (t.t.). Qahaf, Mundzir. Manajemen Wakaf Produktif. Jakarta: Khalifa, 2005. “Undang-undang (UU) Nomor.18 Tahun 2019.” JDIH BPK RI, 16 Oktober 2019. Zainal, Veithzal Rivai. “Pengelolaan dan Pengembangan Wakaf Produktif.” Badan Wakaf Indonesia 9 (Januari 2016).